Acupuncture at Neiguan suppresses PVCs occurring post-myocardial infarction by alleviating inflammation and fibrosis - Hao Hong; Xin Cao; Tian Deng; Xiang-Min Meng; Yu-Meng Li; Li-Juan Zhu; Jing Lv; Xuan Li; Shu-Guang Yu; Bing-Mei Zhu (BMC, 2022)
Abstract Background Acupuncture at Neiguan (PC6) has long been used for treating cardiovascular diseases, but its antiarrhythmic effect and the underlying mechanisms have not yet been well investigated, especially regarding premature ventricular complexes (PVCs) that occur post-myocardial infarction (MI). The purpose of this study was to study the antiarrhythmic effect of manual acupuncture applied to PC6 for a relatively long period (28 days) and to elucidate the mechanism in mice. Methods An MI mouse model was generated by ligating the left anterior descending coronary artery in male C57/BL6 mice (n = 31). Manual acupuncture at PC6 was applied seven times weekly for 4 weeks. The state of myocardial injury was characterized by electrocardiography (ECG) and echocardiography. Inflammation was detected by ELISA and immunohistochemical stanning. Fibrosis was evaluated by Masson's trichrome staining. RNA sequencing was used to explore the differentially expressed genes (DEGs) among the different groups after treatment. Results Acupuncture at PC6 lowered the incidence of spontaneous PVCs after MI injury (1/9, 11%) compared to that in mice without acupuncture treatment (6/9, 67%) and improved the ejection fraction from 31.77% in the MI mice to 44.18% in the MI + PC6 mice. Fibrosis was reduced after PC6 treatment. RNA-seq showed many DEGs involved in the immune system and inflammatory response pathway. Further studies confirmed that inflammation at the circulation level and cardiac tissue was inhibited in MI + PC6 mice, accompanied by suppressed sympathetic activation. Conclusions In conclusion, 28-day treatment of acupuncture at PC6 reduced spontaneous PVCs and improved systolic function, possibly by suppressing inflammatory response-mediated fibrosis and sympathetic hyperactivity.